Sustainable agricultural practice and environmental development of Goiás - Barbosa, Danilo Pereira; Salustiano, Sílvia Ferreira Marques; Borges, Nívea Rodrigues; Silva, Jesiel Souza; Ouro-Salim, Omar (Brazilian Journal of Production Engineering, 2025)
Considering the strategic role of the state of Goiás in the Brazilian economy and its impact on environmental development, this research assesses agricultural sustainability in the state by examining the formation of clusters. Using the hierarchical clustering methodology, municipalities were grouped according to the following variables: legal reserve area, permanent preservation, water deficit, pasture conditions, organic production, and sustainable agricultural practices. The application of the Random Forest algorithm identified sustainable farming practices as the most impactful variable in differentiating the groups. The results indicate that only 12% of municipalities in Goiás have high rates of rural properties adopting sustainable agricultural practices, with family farming being a determining factor for this adherence. Regional disparities show that while some areas, such as Catalão, Jataí, and Rio Verde, exhibit greater integration with sustainable production chains, other regions face structural barriers that hinder the adoption of these practices. Considering these findings, the research underscores the importance of targeted public policies, such as PRONAF, CAF, and incentive programs, in integrating practices like family farming, which can amplify the impact of sustainable practices in the state. The implementation of strategies that incorporate conventional management with sustainable techniques is crucial to enhancing agricultural sustainability and promoting a balance between economic development and environmental preservation.
Keywords: sustainable rural development; organic production; conservation of natural resources; environmental development; hierarchical cluster; random forest